2008
DOI: 10.1111/j.1600-6143.2008.02213.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentrism Is an Unacceptable Rationale for Health Care Policy: A Critique of Transplant Tourism Position Statements

Abstract: Medical tourism has emerged as a global health care phenomenon, valued at $60 billion worldwide in 2006. Transplant tourism, unlike other more benign forms of medical tourism, has become a flashpoint within the transplant community, underscoring the uneasy relationships among science, religion, politics, ethics and international health care policies concerning the commercialization of transplantation. Numerous professional associations have drafted or issued position statements condemning transplant tourism. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The authors found very little research had been completed on the health impact of organ removal on the vendors and suggest that there is little or no medical follow-up for the donors. [32][33][34] The concept of informed consent is integral to an individual's self-determination and participation in wellness. Katz 35 asserts that informed consent is important because the patient must understand the variety of options available to him or her, and the healthcare profession has a moral imperative to help the patient understand the benefits and the harm that may come from his or her choices.…”
Section: Informed Consentmentioning
confidence: 99%
“…The authors found very little research had been completed on the health impact of organ removal on the vendors and suggest that there is little or no medical follow-up for the donors. [32][33][34] The concept of informed consent is integral to an individual's self-determination and participation in wellness. Katz 35 asserts that informed consent is important because the patient must understand the variety of options available to him or her, and the healthcare profession has a moral imperative to help the patient understand the benefits and the harm that may come from his or her choices.…”
Section: Informed Consentmentioning
confidence: 99%
“…Countries differ in their local, cultural, and socio-political circumstances which can inhibit the adoption of a "one size fits all" punitive response imposed through a Western design [52]. Examples of alternative, harmreductionist strategies could involve not only the removal of punishments for sellers, but also of buyers and whistle-blowers, and enhancing their protection.…”
Section: Improving the Response To Organ Tradementioning
confidence: 99%
“…Although, medical tourists often take advantage of vacation activities, their primary objective is healthcare (Bookman & Bookman, ). Evans () reports medical tourism in 2006 was a $60 billion industry worldwide.…”
mentioning
confidence: 99%
“…Lower healthcare cost is commonly cited as motivation for medical tourism, with patients finding a 40% to 90% savings in the international healthcare market for comparable procedures (Bookman & Bookman, ; Burkett, ; Merrell et al, ). Medical tourists also travel to avoid wait times for elective procedures in their countries of origin (Evans, ; Leahy, ). The ability to obtain new or experimental treatments not obtainable within the country of residence may also motivate medical tourists (Blythe & Farrand, ; Lindvall & Hyun, ; Spar, ).…”
mentioning
confidence: 99%